The Evaluation of Indicators Used to Assess the Suitability of Agricultural Waste for Fermentation - Suchowska-Kisielewicz, Monika (Int J Environ Res Public Health, 2019)
To ensure high fermentation efficiency, it is necessary to assess the biodegradability of a substrate. These parameters are most often determined on the basis of the amount of loss on ignition and total organic carbon. We are more and more often using chemical indices. However, these indices do not provide information on how much an organic substance is susceptible to biodegradation. The actual assessment of the content of easily biodegradable matter in substrates that are used for fermentation should be performed on the basis of aerobic (AT4) and anaerobic tests (BMP), which require specialised equipment and are time consuming. The AT4 index is being more and more frequently adopted for the analysis of substrates that are used in the fermentation process, because AT4 takes a much shorter time than BMP and provides information on the biodegradability of substrates. The aim of the article is to answer the question of whether the AT4 parameter can be used to assess the suitability of the substrate from the agricultural sector for the fermentation process. The results show that the AT4 index could be used instead of the BMP parameter.